A Molecular Dynamics Simulation Study of Amine-Carboxyl Ionic Interactions and Their Distribution in a Polysiloxanes Network. Issue 6 (3rd October 2022) - Wu, Weijian; Shan, Shijie; Zhao, Haojie; Lin, Yaling; Zhang, Anqiang
Abstract: The ionic crosslinking mechanism of polysiloxanes networks based on amine/carboxyl interactions was investigated by molecular dynamics and tensile performance experiments. The "one-chain-crosslinking" mechanism between crosslinkers and polymers was investigated based on the corresponding simulations. The experimental results showed that the tensile strength and elongation at break of amine-functional polysiloxanes (AFPs)/carboxyl-functional polysiloxanes (CFPs) (1.54 MPa@264%, respectively) were higher than that of amine and carboxyl-functional polysiloxanes (ACFPs) (0.66 MPa@45%). The simulation results indicated that the number of intrachain and interchain hydrogen bonds played an important role for improving the mechanical performance of the polymer networks. In addition, it was found that the orientation and entanglement of the polymer chains had a direct correlation with hydrogen bonding in the equilibrium state and during the stretching process. The mean square radius of gyration ( R g 2), the mean square end-to-end distance ( R ee 2), the orientation parameter, the entanglement parameter, and the mean square displacement (MSD) of the chains in the equilibrium state were calculated. The molecular dynamic simulations were verified by comparing the simulated results with the tensile and rheological experimental results of the AFPs/CFPs and ACFPs elastomers.